Heat stress induced changes in protein profile of Indian mustard (Brassica juncea L.) - Babita Rani,; Nisha Kumari,; Veena Jain,; Kamal Dhawan,; Ram Avtar, (Journal of Oilseed Brassica, 2026)
The present investigation was undertaken to study the changes in protein pattern of seedlings of Indianmustard (Brassica juncea L.) after subjecting to high temperature stress (45±0.5°C) and on revival. Twothermo-tolerant genotypes including BPR-542-6 and NRCDR-02 and two thermo-susceptible genotypesincluding NPJ-119 and RGN-152 were screened at 45±0.5°C on the basis of time taken to 50% seedlingmortality and protein pattern of the seedlings was determined by SDS-PAGE. A major band of 53.12 kDa andminor bands of 100, 89.12, 74.13, 46.76 and 38.9 kDa in thermo-tolerant genotypes and protein bands ofmolecular weight 25.79 and 30.7 kDa in thermo-susceptible genotypes appeared under high temperaturestress which disappeared when the stress was relieved. The newly synthesized proteins might be stressrelated proteins (heat shock proteins) which may play active role in imparting thermo-tolerance.